A Comparative Dialectical Study of Genitive Constructions in Aramaic Translations of Exodus - Meyer, Mark (Perspectives on Linguistics and Ancient Languages, 2012)
This book uses the multiple Aramaic translations of Exodus to reveal important similarities and differences between five Aramaic dialects in the use of genitive constructions: the Syriac Peshitta, Targum Onkelos, three corpora of the Palestinian Targum, the Samaritan Targum, and fragments of a Christian Palestinian Aramaic translation of Exodus